ANALISA PERENCANAAN PONDASI TIANG PANCANG PADA GEDUNG REKTORAT UNIVERSITAS DARUL ULUM JOMBANG - Mualif Mualif; Ahmad Ridwan; Sigit Winarto (Faculty of Engineering, Kadiri University, 2020)
The building is a physical form of the results of construction work that integrates with its domicile. The building functions as a place to live and as a public place like a place of education. As is the case with buildings in general, Darul Ulum University's Rectorate Building in Jombang has a variety of functions, including a venue for various activities both for the chancellor, education staff, and students. In this research, the writer wants to plan the construction of Darul Ulum University, Jombang University Building, with a pile foundation using the Guy Sangrelat method based on SPT data obtained from the project construction site. The pile foundations' design received a vertical load of 36 tons, carrying capacity of a single pile of 12.23 tons, carrying capacity of a group pile foundation of 37 tons, carrying capacity of a pile foundation 37 tons greater than the load that rests on the foundation. The foundation plan used in the Darul Ulum Jombang University Rectorate Building construction is to use a 30 cm diameter pile with a depth of 9.6 meters.Gedung merupakan wujud fisik hasil pekerjaan konstruksi yang menyatu dengan tempat kedudukannya. Gedung berfungsi sebagai tempat hunian dan sebagai tempat umum seperti tempat pendidikan. Seperti halnya dengan Gedung pada umumnya, Gedung Rektorat Universitas Darul Ulum Jombang mempunyai berbagai fungsi meliputi tempat terselenggaranya berbagai kegiatan baik untuk rektor, tenaga kependidikan maupun kemahasiswaan. Pada penelitian ini penulis ingin merencanakan pembangunan Gedung Rektorat Universitas Darul Ulum Jombang dengan pondasi tiang pancang dengan metode Guy Sangrelat berdasar data SPT yang diperoleh dari lokasi pembangunan proyek. Rencana pondasi tiang pancang didapatkan beban vertical sebesar 36 ton, daya dukung tiang tunggal sebesar 12.23 Ton, daya dukung pondasi tiang kelompok sebesar 37 ton, daya dukung pondasi tiang pancang 37 Ton lebih besar dari beban yang menumpu pada pondasi. Rencana pondasi yang digunakan pada pembangunan Gedung rektorat Universitas Darul Ulum Jombang adalah menggunakan tiang pancang berdiameter 30 cm dengan kedalaman 9.6 meter.